CBLB ablation with CRISPR/Cas9 enhances cytotoxicity of human placental stem cell-derived NK cells for cancer immunotherapy. Issue 3 (19th March 2021) - Guo, Xuan; Mahlakõiv, Tanel; Ye, Qian; Somanchi, Srinivas; He, Shuyang; Rana, Hemlata; DiFiglia, Andrea; Gleason, Joseph; van der Touw, William; Hariri, Robert; Zhang, Xiaokui
Abstract : Background: Tumors often develop resistance to surveillance by endogenous immune cells, which include natural killer (NK) cells. Ex vivo activated and/or expanded NK cells demonstrate cytotoxicity against various tumor cells and are promising therapeutics for adoptive cancer immunotherapy. Genetic modification can further enhance NK effector cell activity or activation sensitization. Here, we evaluated the effect of the genetic deletion of ubiquitin ligase Casitas B-lineage lymphoma pro-oncogene-b ( CBLB ), a negative regulator of lymphocyte activity, on placental CD34 + cell-derived NK (PNK) cell cytotoxicity against tumor cells. Methods: Using CRISPR/Cas9 technology, CBLB was knocked out in placenta-derived CD34 + hematopoietic stem cells, followed by differentiation into PNK cells. Cell expansion, phenotype and cytotoxicity against tumor cells were characterized in vitro. The antitumor efficacy of CBLB knockout (KO) PNK cells was tested in an acute myeloid leukemia (HL-60) tumor model in NOD- scid IL2R gamma null (NSG) mice. PNK cell persistence, biodistribution, proliferation, phenotype and antitumor activity were evaluated. Results: 94% of CBLB KO efficacy was achieved using CRISPR/Cas9 gene editing technology. CBLB KO placental CD34 + cells differentiated into PNK cells with high cell yield and >90% purity determined by CD56 + CD3 − cell identity. Ablation of CBLB did not impact cell proliferation, NK cell differentiation or phenotypical characteristics of PNK cells. When compared with the unmodified PNK control, CBLB KO PNK cells exhibited higher cytotoxicity against a range of liquid and solid tumor cell lines in vitro. On infusion into busulfan-conditioned NSG mice, CBLB KO PNK cells showed in vivo proliferation and maturation as evidenced by increased expression of CD16, killer Ig-like receptors and NKG2A over 3 weeks. Additionally, CBLB KO PNK cells showed greater antitumor activity in a disseminated HL60-luciferase mouse model compared with unmodified PNK cells. Conclusion: CBLB ablation increased PNK cell effector function and proliferative capacity compared with non-modified PNK cells. These data suggest that targeting CBLB may offer therapeutic advantages via enhancing antitumor activities of NK cell therapies.